2007
DOI: 10.1002/jms.1349
|View full text |Cite
|
Sign up to set email alerts
|

Rapid characterization of covalent modifications to rat brain mitochondrial proteins after ex vivo exposure to 4‐hydroxy‐2‐nonenal by liquid chromatography–tandem mass spectrometry using data‐dependent and neutral loss‐driven MS3 acquisition

Abstract: The modification of mitochondrial proteins enriched from rat forebrain by the major lipid peroxidation product 4-hydroxy-2-nonenal (HNE) was investigated using high performance liquid chromatography (HPLC) and tandem mass spectrometry. Subcellular fractionation in conjunction with a 'shotgun-based' approach that involved both conventional data-dependent and neutral loss (NL)-driven MS(3) data acquisition on a hybrid linear ion trap-Fourier transform ion cyclotron resonance mass spectrometer (LTQ-FT) was utiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 33 publications
0
47
0
Order By: Relevance
“…SPH chemistry of peptide carbonyls [35,36] permitted the removal of non-modified species and, thereby, facilitated the identification of HNE-modified peptides in the proteome. We have previously shown that this enrichment technique significantly improved the quality of MS/MS spectra by increasing the number of ion counts and reducing interference during precursor-ion isolation and fragmentation in brain derived mitochondria [23,36]. We, again, utilized this enrichment method in this study to “fish-out” peptide carbonyls from the tryptic digest of HNE-treated mitochondria protein fraction of the rat liver for modification-directed identification.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…SPH chemistry of peptide carbonyls [35,36] permitted the removal of non-modified species and, thereby, facilitated the identification of HNE-modified peptides in the proteome. We have previously shown that this enrichment technique significantly improved the quality of MS/MS spectra by increasing the number of ion counts and reducing interference during precursor-ion isolation and fragmentation in brain derived mitochondria [23,36]. We, again, utilized this enrichment method in this study to “fish-out” peptide carbonyls from the tryptic digest of HNE-treated mitochondria protein fraction of the rat liver for modification-directed identification.…”
Section: Resultsmentioning
confidence: 97%
“…Due to its chemical nature, HNE easily undergoes Michael addition on the side chain functional group of Cys, His, and Lys, respectively [19]. It can also produce Schiff bases with the ε-amino group of Lys, but the corresponding kinetics are inherently slow and Schiff-base formation is also reversible [20,21] making Michael-adducts of HNE the predominant [2123] and most reliable products for exploring protein carbonylation through proteomics [21,23,24]. …”
Section: Introductionmentioning
confidence: 99%
“…In most cases, the specific modification sites were identified and the consequent biological effects were elucidated. ONE-and HNE-modified proteins have also been found in human red blood cells [36], liver fractions from a rat model of chronic alcoholic disease [37], rat brain tissues [38], and adipose tissues from obese insulin-resistant mice [39]. However, the identification of adduction sites was often challenging because of complex biological matrices and required in vitro experiment using recombinant proteins.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a nerve agent exposure will result in the formation of adducts to human butyryl cholinesterase (HuBuChE) [5], whereas the vesicant sulfur mustard will give rise to rather random adducts, e.g., to human serum albumin (HSA) [6][7][8]. Similar covalent protein adducts are often observed in drug toxicology (see, e.g., [9][10][11]), in metabolism (e.g., [12][13][14][15][16]) and from post-translational modification (e.g., [17,18]). The analysis of covalent protein adducts is usually performed by enzymatic digestion of the modified protein and subsequent mass spectrometric analysis of the resultant peptide or amino acid adducts.…”
Section: Introductionmentioning
confidence: 94%